2021
DOI: 10.1371/journal.pone.0252111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impacts of land use/land cover changes across topography against land surface temperature in Cameron Highlands

Abstract: The Cameron Highlands has experienced multiple land encroachment activities and repeated deforestation, leading to extensive land-use and land-cover change (LULCC) during the past six decades. This study aims to determine the LULCC against topography in Cameron Highlands between 2009 and 2019 by using geospatial techniques to analyze Landsat 7 (ETM+) and 8 (OLI/TIRS), ASTER GDEM and MODIS imaging sensors. The results showed a decline of 35.98 km2 in primary forests over ten years across the Cameron Highlands, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 62 publications
2
8
0
Order By: Relevance
“…The present research showed an increase in temperature by roughly 2.3-3.0 • C in 10 years in DDWS. This findings support the research of Aik et al (2021) on Cameron Highlands, where a rise in temperature found 2.0-3.5 • C in each decade and the increase was introduced by conversion of forest cover in to urban and urban in to agriculture. Choudhury et al (2019) also reported similar research findings, where the land surface temperature increased from 0.6 to 4.3 • C per decade.…”
Section: Discussionsupporting
confidence: 90%
“…The present research showed an increase in temperature by roughly 2.3-3.0 • C in 10 years in DDWS. This findings support the research of Aik et al (2021) on Cameron Highlands, where a rise in temperature found 2.0-3.5 • C in each decade and the increase was introduced by conversion of forest cover in to urban and urban in to agriculture. Choudhury et al (2019) also reported similar research findings, where the land surface temperature increased from 0.6 to 4.3 • C per decade.…”
Section: Discussionsupporting
confidence: 90%
“…In summary, as indicated in Figure 3, the agricultural areas stretched to a higher altitude. This result is consistent with previous studies conducted to evaluate the impacts of LULC with topography [65]. The extent of different LC types and their rate of change during the study period are summarized in Table 2.…”
Section: Land Cover Changesupporting
confidence: 91%
“…The spatial patterns of LULC change across administrative zones were obtained from an overlay procedure of the LULC maps with the polygons of parishes from the studied Pedro Moncayo county, which were downloaded from the official reference [44]. In the same way, to understand the patterns of LULC change across elevation classes, first the National Digital Elevation Model at a 30 m spatial resolution [45] was clipped to the study area, after that, the resulting image was further reclassified according to elevation bands, with an interval of 500 m [46,47], resulting in the following four elevation bands <2300, 2300-2800, 2800-3300, >3300 (Fig 1); these groupings take into consideration the mean medium of relief surface roughness, type of forests and the presence of urban areas [46]. Finally, the LULC classification for each year was layered over both (1) the reclassified elevation map, and the (2) reclassified administrative map.…”
Section: Land Use and Cover Changesmentioning
confidence: 99%